Planet migration, resonant locking, and accretion streams in PDS 70: comparing models and data. Issue 2 (25th September 2020) - Toci, Claudia; Lodato, Giuseppe; Christiaens, Valentin; Fedele, Davide; Pinte, Christophe; Price, Daniel J; Testi, Leonardo
ABSTRACT: The disc surrounding PDS 70, with two directly imaged embedded giant planets, is an ideal laboratory to study planet–disc interaction. We present 3D smoothed particle hydrodynamics simulations of the system. In our simulations, planets, which are free to migrate and accrete mass, end up in a locked resonant configuration that is dynamically stable. We show that features observed at infrared (scattered light) and millimetre (thermal continuum) wavelengths are naturally explained by the accretion stream on to the outer planet, without requiring a circumplanetary disc around Planet c. We post-processed our near-infrared synthetic images in order to account for observational biases known to affect high-contrast images. Our successful reproduction of the observations indicates that planet–disc dynamical interactions alone are sufficient to explain the observations of PDS 70.